Comparative study of high-intensity laser therapy versus low-intensity laser therapy as an add-on therapy in chronic myofascial pain syndrome at upper trapezius; randomized controlled trial - Topanyarueang, Thanaphon; Arayawichanon, Preeda; Jitpimolmard, Nantaporn (Asia-Pacific Journal of Science and Technology, 2025)
The study compared the effects of high-intensity laser therapy (HILT) and low-intensity laser therapy (LILT) for treating patients with chronic myofascial pain syndrome in the upper trapezius muscle through a randomized controlled trial. Eligible participants were randomly assigned to either the HILT (n=30) or LILT (n=30) groups. Both groups were instructed to perform daily home-based muscle stretching exercises. HILT or LILT was administered twice a week for four weeks based on the assigned group. The study assessed pain score, cervical range of motion, and pressure pain threshold of the upper trapezius muscle at baseline, after the first session, after treatment, and four weeks after treatment. Results showed all outcomes significantly improved in both groups over the measured period. However, no significant differences were found between groups. The study concluded that HILT combined with home-based stretching exercises did not yield superior clinical outcomes compared to LILT combined with home-based stretching exercises.